1996
DOI: 10.1021/ma961104q
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Polymerizations in Two-Dimensional Assemblies

Abstract: Polymerization of monomeric lipids in an assembly proceeds in a linear or cross-linking manner depending on the number of polymerizable groups per monomeric lipid. Lipids that contain a single reactive moiety in either of the hydrophobic tails or associated with the hydrophillic head group yield linear polymers. Polymerization of lipids with reactive groups in each hydrophobic tail generally yield cross-linked polymeric networks. This report describes three approaches to the characterization of the gel point f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
135
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(144 citation statements)
references
References 52 publications
5
135
0
4
Order By: Relevance
“…Although cross-linked PSLBs are formed by both methods, previous studies on poly(bis-SorbPC) vesicles have shown that redox initiation produces a greater degree of polymerization (X n = 50-500) than UV irradiation (X n = 3-10). [32][33][34] A similar trend likely occurs in bis-SorbPC PSLBs polymerized by these two methods, and significant differences in their respective structural properties have been observed. 14,15 The origin of these differences may be different propagation mechanisms for the two methods.…”
Section: Xps Of Uv-and Redox-polymerized Bis-sorbpc Bilayersmentioning
confidence: 54%
“…Although cross-linked PSLBs are formed by both methods, previous studies on poly(bis-SorbPC) vesicles have shown that redox initiation produces a greater degree of polymerization (X n = 50-500) than UV irradiation (X n = 3-10). [32][33][34] A similar trend likely occurs in bis-SorbPC PSLBs polymerized by these two methods, and significant differences in their respective structural properties have been observed. 14,15 The origin of these differences may be different propagation mechanisms for the two methods.…”
Section: Xps Of Uv-and Redox-polymerized Bis-sorbpc Bilayersmentioning
confidence: 54%
“…38 The onset of cross-linking was determined by changes in lipid lateral diffusion, bilayer vesicle stability, and polymer solubility. These data indicated that a substantial mole fraction (0.30 ± 0.05) of the bis-SorbPC, as in the case of AcrylPC (see section II.A), was necessary for bilayer crosslinking.…”
Section: B Dienoyl Sorbyl and Diene Monomersmentioning
confidence: 99%
“…Upon polymerization, the bilayers became significantly less soluble in organic solvents or detergent solutions. [17][18][19][20] In addition, decrease in the lateral diffusion constant and the permeation coefficient of the bilayers was observed. 21,22 Micropatterning of SPBs by lithographic photopolymerization of lipid bilayers aims to achieve both spatial control and stabilization of biomimetic membranes.…”
Section: Introductionmentioning
confidence: 97%